RELATIONSHIP BETWEEN PSYCHOLOGICAL WELL-BEING AND SOCIAL SUPPORT WITH THE PERFORMANCE OF PAUD TEACHERS IN KARO DISTRICT - Diana Stevani Br Tarigan; Nefi Darmayanti; Amanah Surbakti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The performance of early childhood teachers currently has many problems in implementing learning services. The performance of early childhood teachers is certainly influenced by many factors. This study aims to analyze and determine the relationship between psychological well-being and social support with the performance of PAUD teachers. This research is included in the quantitative associative causal research. The sample for this study was 153 PAUD teachers spread across 16 sub-districts in Karo District. Research data was collected using a research scale that was declared valid and reliable. Technical data analysis using multiple linear regression analysis. The results of the study show that (1) there is a relationship between psychological well-being and teacher performance. From the results of statistical analysis, it was found that the correlation coefficient rx1y was 0. 262 with p <0.05, this means that the level of psychological well-being possessed by the teacher will be able to increase or decrease his performance. (2) there is a relationship between social support and teacher performance. From the results of statistical analysis it was found that the correlation coefficient rx2y was 0.572 with p <0.05, thus it can be concluded that the amount of social support received by teachers will be able to increase or decrease their performance. (3) there is a relationship between psychological well-being and social support with teacher performance. From the results of statistical analysis it was found that the coefficient F reg = 28.539 with p < 0.05, and the correlation coefficient R = 0.593 with p < 0.05 and R2 = 0.352. Thus it can be concluded that psychological well-being and social support together have an effect on teacher performance,